Hurford Conditionals. (26th March 2018) - Mandelkern, Matthew; Romoli, Jacopo
Abstract: Compare the following conditionals: Bad #If John is not in Paris, he is in France. Good If John is in France, he is not in Paris. Good sounds entirely natural, whereas Bad sounds quite strange. This contrast is puzzling, because Bad and Good have the same structure at a certain level of logical abstraction: (1) If ¬ p +, then p . We argue that existing theories of informational oddness do not distinguish between Bad and Good . We do not have an account of the divergence in judgments about the two, but we think this is a fascinating puzzle which we pose here in the hope others will be able to solve it.